The readability, suitability, and content features of eczema action plans in the United States. Issue 6 (15th October 2018) - Stringer, Thomas; Yin, H. Shonna; Gittler, Julia; Curtiss, Paul; Schneider, Amanda; Oza, Vikash S.
Abstract: Background/Objectives: Little is known about the reading grade level (readability), appropriateness of design (suitability), and content variability of written eczema action plans (EAPs), which can impact the effectiveness of these patient education tools. Here, we assess the readability, suitability, and content of EAPs currently used by pediatric dermatologists in the United States. Methods: This was a cross‐sectional study of EAPs submitted by members of the Society for Pediatric Dermatology (n = 26). Readability, suitability, and content of sampled plans were systematically assessed. Results: Mean (SD) reading grade level was 9.0 (2.1); one in five was written at the recommended level of 6th grade or lower. While the majority of EAPs were found to be adequately suitable, one in five was unsuitable and only two superior. Documents scored most poorly in layout/design and learning stimulation. Plans scored best in the categories of content and literacy demand. EAPs focused on similar content themes, though specific recommendations and descriptors of atopic dermatitis (AD) disease states varied considerably. Conclusions: The health literacy burden of EAPs in the United States could be lowered by improving their readability, incorporating graphics, stimulating reader engagement, and developing standards for how AD flares are defined.